Paradigma Kedaulatan Pangan Sebagai Landasan Penanggulangan Krisis Pangan Global Dalam Perspektif Negara Hukum Kesejahteraan - Hotma P. Sibuea; Indra Lorenly Nainggolan; Jantarda Mauli Hutagalung (KRTHA BHAYANGKARA, 2022)
The Indonesian Constitution stipulates in Article 28H paragraph (1) as follows: “everyone has the right to live in physical and spiritual prosperity, to live and to have a good and healthy environment, and to have the right to health services”. The principle of a prosperous life as the right of every person is further regulated in Article 9 paragraph (2) of Law Number 39 of 1999 which stipulates as follows ” everyone has the right to live in peaceful, safe, peace, happy, physical and spiritual prosperity. One aspect of supporting a prosperous life is food. Food is one of the basic human needs that must be met in order to live a prosperous life. The Indonesian state and nation really understand the urgency of food in human life so that they can live in prosperity. Based on the idea of the urgency of food in a prosperous human life, Indonesia stipulates Law No. 18 of 2002 on Food. The Indonesian state is determined to achieve the ideals of "food sovereignty" as an ideal condition that is expected to support the welfare of the Indonesian nation. The Indonesian people are determined to be sovereign in the food sector in the sense of having the ability to determine food policies that guarantee the right to food so that the Indonesian people can live in prosperity. However, in reality, the world is experiencing a food crisis at this time. The reality of the food crisis that is hitting the world at this time is one of the agendas promoted by President Joko Widodo, who serves as the G-20 Presidency, as one of the main agendas of the G-20 meeting in the months ahead. Can President Joko Widodo as the G-20 Presidency garner the agreement of G-20 countries to cooperate and work together to overcome the world food crisis as one of the main agendas of the G-20 meeting? This research uses juridical-normative research methods and other research methods that are deemed necessary and can support the success of the research. According to the author, as the G-20 Presidency, President Joko Widodo will be able to forge an agreement with G-20 member countries to work together and work together to overcome the world food crisis that is happening at this time. The reason is that all G-20 member countries and all countries in the world will be affected by the global food crisis in due time, so if they do not want to be affected by the global food crisis, all G-20 member countries and the other countries on the surface of the earth must work together to tackle the global food crisis. All G-20 member countries are advised to take concrete steps to overcome the food crisis in their respective countries as has been done by Indonesia as stated in President Joko Widodo's program.